Evolution of colour vision in mammals - Jacobs, Gerald H (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 2009)
Colour vision allows animals to reliably distinguish differences in the distributions of spectral energies reaching the eye. Although not universal, a capacity for colour vision is sufficiently widespread across the animal kingdom to provide prima facie evidence of its importance as a tool for analysing and interpreting the visual environment. The basic biological mechanisms on which vertebrate colour vision ultimately rests, the cone opsin genes and the photopigments they specify, are highly conserved. Within that constraint, however, the utilization of these basic elements varies in striking ways in that they appear, disappear and emerge in altered form during the course of evolution. These changes, along with other alterations in the visual system, have led to profound variations in the nature and salience of colour vision among the vertebrates. This article concerns the evolution of colour vision among the mammals, viewing that process in the context of relevant biological mechanisms, of variations in mammalian colour vision, and of the utility of colour vision.